Evaluasi Kualitas Ruang Pedestrian di Kawasan Ciputat Timur dengan Parameter Walkability - Kapindro Hari Sasmita; Annisa Marwati (Lakar: Jurnal Arsitektur, 2023)
By the middle of this century two thirds of the world’s population are expected to be living in urban centres. Without sustainable mobility concepts that include public transport as well as non-motorized transport, cities will collapse under the burden of traffic jams, polluted air and noise (Müller, 2016). According to Global Designing Cities Initiative 2016, the walkable, cyclable, and transit-oriented neighborhoods are what today’s urban dwellers need and demand. Daily traffic happened in East Ciputat Region, South Tangerang City, is affected by its strategic position and also by dependance of local people on private motor vehicles for their daily activities. The lack of good pedestrian space makes people not willing to get around by walking even though their destinations are actually convenient enough from their homes. This research is aimed to evaluate the planning quality of pedestrian space in the East Ciputat Region on supporting daily mobility by walking as a fundamental transportation tool. Evaluative-qualitative method is utilized in this research by doing a direct observation on the site. The assessment parameter is theories related to walkability. The novelty of this research is identifying how arrangement of sidewalk space zoning affecting the walkability in East Ciputat area. Then it could be generated that low quality of pedestrian space in the area is caused by unavailability of regular placement for the street furniture zone and frontage zone, and also the lack of maintenance for Culvert Box structure as its main groundcover. The result of the research is expected to be evaluation for government and city planners in arranging city corridors to be more walkable.